Potential of laryngeal muscle regeneration using induced pluripotent stem cell-derived skeletal muscle cells. (2nd April 2016) - Dirja, Bayu Tirta; Yoshie, Susumu; Ikeda, Masakazu; Imaizumi, Mitsuyoshi; Nakamura, Ryosuke; Otsuki, Koshi; Nomoto, Yukio; Wada, Ikuo; Hazama, Akihiro; Omori, Koichi
ABSTRACT: Conclusion Induced pluripotent stem (iPS) cells may be a new potential cell source for laryngeal muscle regeneration in the treatment of vocal fold atrophy after recurrent laryngeal nerve paralysis.Objectives Unilateral vocal fold paralysis can lead to degeneration, atrophy, and loss of force of the thyroarytenoid muscle. At present, there are some treatments such as thyroplasty, arytenoid adduction, and vocal fold injection. However, such treatments cannot restore reduced mass of the thyroarytenoid muscle. iPS cells have been recognized as supplying a potential resource for cell transplantation. The aim of this study was to assess the effectiveness of the use of iPS cells for the regeneration of laryngeal muscle through the evaluation of both in vitro and in vivo experiments.Methods Skeletal muscle cells were generated from tdTomato-labeled iPS cells using embryoid body formation. Differentiation into skeletal muscle cells was analyzed by gene expression and immunocytochemistry. The tdTomato-labeled iPS cell-derived skeletal muscle cells were transplanted into the left atrophied thyroarytenoid muscle. To evaluate the engraftment of these cells after transplantation, immunohistochemistry was performed.Results The tdTomato-labeled iPS cells were successfully differentiated into skeletal muscle cells through an in vitro experiment. These cells survived in the atrophied thyroarytenoid muscle after transplantation.